THE STRONG AND STABLE UPWELLING AND DOWNWELLING REGIONS IN THE ECMAN LAYER OF THE SOUTH CHINA SEA - Lanh, Vo Van; Son, Tong Phuoc Hoang; Tuan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2007)
On the  basis of distribution of curl (τ/f) computed by the means monthly data of wind and relationship  between the  curl (τ/f) with the vertical velocity W [equation (5)], the  regions of upwelling [Rot(τ/f) >  0, W  < 0] and downwelling [Rot(τ/f) < 0, W > 0] in the Ecman layer of South China Sea were determined. The  results indicates that the upwelling and downwelling phenomena are occurred almost everywhere in  the  sea, but  the  most  strong (/W/ ≥ 10-3 cm/s) and stale ones in the following locations: 1. Very strong upwelling in he Southern Central Vietnam coastal and shelf waters during South West Monsoon (Fig. 2). The hydrological analysis indicate that in the centre of the upwelling, the /W/ can  reach to 10-1 – 10-2 cm/s, the water temperature anomaly - to  -3 ÷ -50C and salinity anomaly - to  +1,2%o at the depths of 50 - 100 m. 2. The strong upwelling in the region North West and South West of Luzon island during North East Monsoon, when the water temperature anomaly can reach to -30C and salinity - to +1%o at the depths of 50 – 100 m (Fig. 1). 3. The strong downwelling in the Southern Central Vietnam coastal and shelf waters and in the region South West of Taiwan during North East Monsoon (Fig. 1). τ is the wind stress, f is the Coriolic parameter, W is the vertical velocity.